Opposite T3 Response of ACTG1–FOS Subnetwork Differentiate Tailfin Fate in Xenopus Tadpole and Post-hatching Axolotl - Kerdivel, Gwenneg; Blugeon, Corinne; Fund, Cédric; Rigolet, Muriel; Sachs, Laurent M.; Buisine, Nicolas (Frontiers in Endocrinology, 2019)
Amphibian post-embryonic development and Thyroid Hormones (TH) signaling are deeply and intimately connected. In anuran amphibians, TH induce the spectacular and complex process known as metamorphosis. In paedomorphic salamanders, at the onset of limb development, raising levels of TH fail to induce proper metamorphosis, as many “larval” tissues (e.g. gills, tailfin) are maintained. Why does the same evolutionary conserved signaling pathway leads to alternative phenotypes? We used a combination of developmental endocrinology, functional genomics and network biology to compare the transcriptional response of tailfin to TH, in the post-hatching paedormorphic Axolotl salamander and Xenopus tadpoles. We also provide a technological framework that efficiently reduces large lists of regulated genes down to a few, highlighted by their shared functional connections. We first show that Axolotl tailfin undergoes a strong and robust TH-dependent transcriptional response at post embryonic transition, despite the lack of visible anatomical changes. We next show that FOS and ACTG1, which structure a single and dense subnetwork of cellular sensors and regulators, display opposite regulation between the two species. We finally show that TH treatments and natural variations of TH levels follow similar transcriptional dynamics. We suggest that, at the molecular level, tailfin fate correlates with the alternative transcriptional states of an FOS-ACTG1 sub-network, which also includes transcription factors and regulators of cell fate. This subnetwork would be the molecular switch governing the initiation of distinct TH responses, with transcriptional programs conducting alternative tailfin fate (maintenance vs resorption).